PENGARUH FINANCIAL TARGET, PERGANTIAN AUDITOR TERHADAP FINANCIAL STATEMENT FRAUD DENGAN PERGANTIAN DIREKSI SEBAGAI VARIABEL INTERVENING PADA INDUSTRI PERBANKAN INDONESIA - Firmansyah Arifin; Yuni Rachmawati (Fakultas Ekonomi Universitas Tridinanti Palembang, 2022)
This study aims to determine the effect of Financial Target, Change in auditor with the change of directors as an intervening variable on Financial Statement Fraud. This study uses the theory of fraud pentagon. The approach used in this study is a descriptive quantitative approach. The population of this study is banking companies listed on the Indonesia Stock Exchange. The research period in this study is from 2014 to 2019. The data used in this study is secondary data obtained from the company's annual financial statements. A purposive sampling technique was used to determine the research sample. There were 29 companies selected. Data analysis in this study used the path analysis method. Based on the results of the study, it was found that the fraud pentagon theory has an effect on financial statement fraud, especially for auditor turnover in the banking industry listed on the Indonesia Stock Exchange. The high turnover of auditors in a company leads to higher indications of financial statement fraud.Keywords: Financial Target, Change in Auditor, Change in Director, Financial Statement Fraud, Fraud pentagon theory